A study of six forage species of the genus Brachiaria - Monteiro, Maria do Carmo da Costa; Lucas, Enésio Delgado de; Souto, Sebastião Manhães (Pesquisa Agropecuaria Brasileira, 2014)
A dichotomous botanical key is presented for six species of Brachiaria, 5 introduced to Brazil, and one spontaneous. The Brachiarias were grown at the South-Central Institute for Agricultural Research (IPEACS), located in Itaguaí in the lowland areas. The key was based on vegetative characteristics. The species studied were the following: Brachiaria brizantha (Hochst.) Stapf., B. decumbens Stapf., B. dictyonera (Fig. et De Not.) Stapf., B. purpurascens (Raddi) Henr., B. ruziziensis Germ. et Evrard, and Brachiaria sp. (Tanner grass). In addition to the key, a brief description of each species is given.